The three stages of religious decline around the world - Jörg Stolz; Nan Dirk de Graaf; Conrad Hackett; Jean-Philippe Antonietti (Nature Communications)
Abstract Religiosity tends to decline across generations. However, religious decline is more pronounced in some countries and the diminishing aspects of religion vary by context. To explain such variation, we extend the general secular transition model, which proposes that countries undergo a similar process of secularization beginning at different points in time. We explain that secular transition happens in three steps: first, public ritual participation declines; second, the importance of religion to individuals declines; and third, people shed religious affiliation. We test this model using datasets from surveys in 111 countries (Pew Research Center), 58 countries (World Values Survey and European Values Study (WVS/EVS)), and a subset of 17 countries measured in at least five WVS/EVS waves. We show the model fits countries with Christian, Muslim, Hindu, and Buddhist pluralities. While Eastern post-Soviet countries deviate from this pattern, traditionally Muslim countries appear to follow its early stages. However, we recommend caution in interpreting longitudinal claims, due to limited data.